Bidirectional association between alopecia areata and atopic dermatitis: A population‐based cohort study in Taiwan. Issue 12 (21st September 2020) - Wei, Yu‐Hsun; Tai, Ying‐Hsuan; Dai, Ying‐Xiu; Chang, Yun‐Ting; Chen, Tzeng‐Ji; Chen, Mu‐Hong
Abstract: Background: An association between alopecia areata (AA) and atopic dermatitis (AD) has been reported in previous studies. However, the temporality of this relationship remains unclear based on prior cross‐sectional and case‐control studies. Objective: This study aimed to investigate the bidirectional association between AA and AD. Methods: Participants were recruited from the National Health Insurance Research Database of Taiwan. In analysis 1, we included 12 022 AA patients and 48 088 matched controls to assess the association between AA and AD risks. In analysis 2, 40 307 AD patients and 161 228 matched controls were included to assess the association between AD and AA risks. A Cox regression model was used to calculate adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Results: Compared with controls, AA patients had a significantly increased risk of developing AD (aHR: 5.47; 95% CI: 4.76‐6.28) after adjustment for potential confounders. Likewise, AD patients had a significantly increased risk of developing AA (aHR: 6.00; 95% CI: 5.04‐7.14). Conclusions: Our study demonstrated a bidirectional association between AA and AD, suggesting that these two diseases may share common pathogenic mechanisms. This finding has implications for follow‐up and screening of AA patients for AD and vice versa.